Arransemen Lagu Bertemakan Keselamatan Lalu Lintas Untuk Guru PAUD - Alfian Saleh; Muthia Anggraini; Sean Marta Efastri (Universitas Lancang Kuning, 2021)
Kindergarten is located in Bandar Seikijang District which is on the edge of the eastern causeway which is an accident-prone road. In addition, there is no curriculum related to traffic safety in the learning process. In overcoming partner problems, the service team provides solutions in the form of assisting the arrangement of the song with the theme of traffic safety which is applied to the curriculum in schools. The steps for implementing the solutions offered in overcoming these problems are four stages, (1) the preparation, (2) the activity, (3) the simulation and microteaching, and (4) evaluation. From the results obtained there is an increase in the result of 50% of the pretest and posttest questions. Then 85% of participants agreed to increase learning creativity with song media and 75% of participants felt this activity was useful and 85% of teachers really followed the course of the activity and teachers could cerate song lyrics with the theme of traffic safety and directly practice it by means of microteaching.